2013
DOI: 10.2310/jim.0b013e318292fc7d
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral-Arterial Tonometry for Assessing Endothelial Function in Relation to Dietary Habits

Abstract: BackgroundPeripheral-arterial tonometry (PAT) provides, with good reproducibility, measures of nitric oxide–mediated endothelial response, which correlate with flow-mediated dilation (FMD) findings obtained by brachial artery ultrasound. Few data about the ability of exploring endothelial function by PAT in relation to dietary habits are available. The aim of this study was to evaluate natural logarithm of reactive hyperemia index (lnRHI) in subjects referred for primary prevention, in relation to classic risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Ln-RHI values of study population were lower than values found in primary prevention subjects, as reported in previously published data [18,19].…”
Section: Peripheral Arterial Tonometry and Flow Cytometric Analysessupporting
confidence: 80%
“…Ln-RHI values of study population were lower than values found in primary prevention subjects, as reported in previously published data [18,19].…”
Section: Peripheral Arterial Tonometry and Flow Cytometric Analysessupporting
confidence: 80%
“…Wine drinkers have been reported to be less overweight, exercise more, and drink with meals (28), which offers plausible explanations for the observed differences between the studied types of drinks. Additionally, previous studies have suggested that certain components in red wine may improve endothelial function (29,30).…”
Section: Wine and Other Alcoholic Beveragesmentioning
confidence: 99%
“…A serious of studies was performed with the aim to identify potential factors affecting the vascular endothelial function [24,25,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73]. Nevertheless, there were substantial variations at study designs and the groups of patients, which were subjects of interest.…”
Section: Discussionmentioning
confidence: 99%